Analysis of histopathological examination results concerning biopsy material taken during pancreas, liver and kidney cyst drainage - Chorąży, Marek; Nasiek-Palka, Anna; Wiąk, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2007)
In years 1997–2003 the authors performed 555 subcutaneous drainages of pancreas, kidneys and liver cysts under USG control, each time taking a biopsy specimen for histopathological examination. Neoplastic disease was diagnosed in 56 (10.09%) patients. Statistically, more diseases of that kind were diagnosed in the case of pancreas cyst in women than in men. In the kidney and liver, also depending on age, statistical significance was not found. It is concluded that every cyst-like change should evoke oncological alertness and should be drained, histopathologically examined and monitored in specialist centers at least once or, in suspicious cases, several times